THE QUESTION OF IDENTITY IN THE URBAN PLANNING SYSTEM IN MOROCCO - Abdelwahed EL IDRISSI (African Journal on Land Policy and Geospatial Sciences, 2022)
Urban and cultural identity is an extremely interesting and decisive concept in the reflections in the past, present and in the future of the territories.